Imam Bediuzzaman Said Nursi's concept of tolerance and a pillar of moderation and unity - Ahmad H.Osman, Rahmah (2017)
The world is in a state of disarray. While humankind has developed and ‘progressed’ into an era of being a global village and technologically astute, it seems that the human condition has disintegrated into that of being foam on the ocean. Technology, material gains, social status and power, even though having been a human endeavour from the beginning of recorded history and documentation of the first murder in this world, with so many experiences that human beings have gone through as a species and the vast access to information as compared to just a few decades ago, one would have expected us to know better. Looking at the landscape of the world, with its media manipulation, war bent communities, extremist ideologies, greed and basic human rights violations, results in a very pessimistic outlook. As Georg Hegel stated “We learn from history that we do not learn from history.”